Intensive Care Management Following Endovascular Clot Retrieval for Acute Stroke: A Systematic Review of the Literature - Ma, Alice; Moynihan, Gerard; Donaldson, Lachlan H. (Journal of Clinical Interventional Radiology ISVIR, 2019)
There has been an increase in the number of patients requiring ICU care following endovascular clot retrieval (ECR) for acute ischemic stroke (AIS). The authors’ objective was to systematically assess the evidence surrounding postprocedural care of ECR patients in critical care areas. A systematic literature review was conducted examining the critical care management of adult patients following ECR. The preliminary search results were sorted manually by two authors and conflicts were settled by consensus with a third reviewer. References of key papers were also reviewed for studies meeting the inclusion criteria. In addition, the authors sought to identify all relevant practice guidelines from major neurological and critical care societies. Study quality was assessed using the Newcastle Ottawa Quality Assessment Scale for cohort studies. Medline, Embase, Cochrane Central Register of Controlled Trials databases, Web of Science, and bibliographies of retrieved articles were searched. Studies were limited to human subjects and English language. Studies specific to the post ECR population were limited. In the initial Medline search, 3,882 papers were returned. A total of 16 studies met the inclusion criteria. There were also 10 practice guidelines from relevant scientific bodies. The level of evidence for postprocedural care was found to be variable and mostly based on expert opinion and data extrapolated from general stroke and postthrombolysis patients. There is limited evidence guiding the postprocedural care of ECR patients. Given the increase in both the availability and application of ECR, trials looking specifically at how best to care for this patient population are needed.
Keywords: mechanical thrombolysis; balloon embolectomy; thrombectomy; endovascular procedures; intracranial embolism; stroke; brain ischaemia; brain infarction; critical care; intensive care units